Thayeria tapajonica (Characiformes: Characidae), a new species from rio Tapajós basin, Brazil - Moreira, Cristiano R.; Lima, Flávio C.t. (Zootaxa, 2017)
A new species of penguin tetra, Thayeria tapajonica, is described from the rio Tapajós basin. It is most similar to T. boehlkei by presenting a straight midlateral stripe running anteriorly to immediately posterior to the head, while in T. ifati and T. obliqua the midlateral stripe is restricted to the caudal peduncle, merging with an anterodorsal oblique stripe. The new species is restricted to the rio Tapajós basin downriver of the confluence of the rio Juruena and rio Teles Pires, and lower rio Teles Pires, where its distribution overlaps with T. boehlkei.